Aspek Reproduksi Ikan Baung (Hemibagrus Nemurus) Di Sungai Air Gandong Kecamatan Riau Silip Kabupaten Bangka - Deri Aja; Sudirman Adibrata; Andi Gustomi (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2023)
Baung fish (Hemibagrus Nemurus) is a fish native to Indonesian waters favored by the people because of thick flesh, slightly spiny and delicious taste, so it has economic value. Baung fish is difficult to find in the waters of Air Gadong River. This study aims to analyze the reproductive aspects of the baung fish including Sex Ratio, Gonad Index, Gonad Maturity Index (IKG), Gonad Maturity Level (TKG), Fecundity of baung fish in Air gadong river, Pangkal Niur Village, Bangka Regency. This research was conducted from January to June 2021. Sampling was carried out using the porposive sampling method. The results showed that were 25 male and female baung fish during the six months of the study with a sex ratio of 1-1.5. The gonad index value of 0.13 < 0.30 means that the average female baung fish has developed. The IKG value of female baung fish is 0,263-2,400 while that male baung fish is 0,257-0,346. Male baung fish are at TKG I to TKG II, while female baung fish are at TKG I, II and IV. The fecundity of the baung fish is 4901.23-7609.07 eggs. The baung fish has a partial spawning pattern, the fish doesn't spawn at once or take place simultaneously.